A novel antibacterial gold nanoparticle layer with a self-cleaning ability through the production of oxygen bubbles. Issue 22 (16th May 2022) - Liang, Jinwei; Wang, Jinghong; Shen, Xiang; Lu, Benben; Li, Guize; Wang, Hengxiao; Wang, Hongwei; Yuan, Lin
Abstract : An antimicrobial peptide mimetics and catalase modified gold nanoparticle layer showed high antibacterial efficiency and self-cleaning ability through the production of bubbles using bacterial and exogenous hydrogen peroxide. Abstract : Bacterial contamination of medical devices not only constitutes a serious threat to the health of patients, but also promotes the evolution of bacterial drug-resistance. Here, a new strategy to fabricate a highly efficient self-cleaning antibacterial coating is reported. Briefly, a nano-topological structure is formed on the substrate surface by the deposition of a gold nanoparticle layer (GNPL), and then antimicrobial peptide mimetics (AMPMs) with optimized structure and catalase (CAT) are modified on the surface. The optimized AMPMs not only inhibit the growth of over 99% of Escherichia coli and Staphylococcus aureus, but also show excellent inhibition efficiency against MRSA. Meanwhile, the entire surface maintains good biocompatibility. In particular, it is found that CAT can decompose the endogenous hydrogen peroxide released from the bacteria, and generate oxygen bubbles to carry off the bacteria adhered to the surface. This special self-cleaning mechanism greatly reduces the adhesion of bacteria and maintains the high antibacterial efficiency of AMPMs for a long time. Moreover, the surface modification strategy has been proved suitable for several substrates, including soft polymers, metals, and inorganic nonmetallic materials, and has great potential to develop more effectual and safe antibacterial surfaces for medical devices in the future.